Shake table tests of steel towers supporting extremely long-span electricity transmission lines under spatially correlated ground motions. (1st February 2017) - Tian, Li; Gai, Xia; Qu, Bing
Highlights: Spatially correlated ground motions can significantly amplify tower responses. Influence of spatial variation of ground motions should not be ignored in design. No clear correlation exists between tower responses and apparent wave velocities. Flexible tower bases may cause larger tower responses. An empirical model was proposed to obtain conservative estimates of tower responses. Abstract: Transmission lines from electricity transmission systems crossing wide rivers or canyons can have much longer spans (e.g. longer than 1000 m) compared with components from conventional civil structures. Steel towers supporting such extremely long-span transmission lines are unavoidably subjected to spatially correlated ground motions together with the coupling action between supporting towers and transmission lines. However, the influence of spatial variation of ground motions is not considered in current seismic design of the towers supporting extremely long-span transmission lines. This research was focused on an electricity transmission system crossing the 2nd longest river in China (which is also the 5th longest river in the world) to address the influence of spatial variation of ground motions on seismic response of the towers supporting extremely long-span transmission lines. A reduced-scale experimental model of the prototype was tested using shake tables. Spatially correlated ground motions generated taking into account the wave passage effect, the effect of coherency loss and the effect of local site conditions were used as inputs of the shake table tests. It was found that the spatially correlated ground motions can significantly amplify tower responses and such an effect should not be neglected in seismic analysis and design. Based on the test database, an empirical model was proposed to modify the acceleration response, member stress response and top displacement responses of the towers supporting extremely long-span transmission lines from uniform ground motions as conservative estimates of responses of the system under spatially correlated ground motions with the same magnitude.